2019
DOI: 10.1080/1369183x.2019.1610365
|View full text |Cite
|
Sign up to set email alerts
|

‘We don’t worry that much about language’: street-level bureaucracy in the context of linguistic diversity

Abstract: View related articlesView Crossmark data Citing articles: 3 View citing articles 'We don't worry that much about language': street-level bureaucracy in the context of linguistic diversity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Our previous research (Holzinger, 2020;Scheibelhofer & Holzinger, 2018;Scheibelhofer et al, 2020) identified difficulties in handling linguistic diversity-both among AMS clients and within the institution itself-which are evident in the language barriers and pressure experienced by street-level bureaucrats (Lipsky, 1980). In a previous study (Holzinger, 2020) we included input from the AMS' migrant clients and will additionally focus on their perspective in a future research project (the FWF Austrian Science Fund-financed project "Investigating the Social Construction of Deskilling Among 'New' EU Migrants in Vienna"). The ongoing project, however, is concerned with the internal perspective found within the institution; it investigates how AMS staff perceive handling linguistic diversity in their daily work routines as well as the associated problems and (both institutional and individual) solution strategies they describe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research (Holzinger, 2020;Scheibelhofer & Holzinger, 2018;Scheibelhofer et al, 2020) identified difficulties in handling linguistic diversity-both among AMS clients and within the institution itself-which are evident in the language barriers and pressure experienced by street-level bureaucrats (Lipsky, 1980). In a previous study (Holzinger, 2020) we included input from the AMS' migrant clients and will additionally focus on their perspective in a future research project (the FWF Austrian Science Fund-financed project "Investigating the Social Construction of Deskilling Among 'New' EU Migrants in Vienna"). The ongoing project, however, is concerned with the internal perspective found within the institution; it investigates how AMS staff perceive handling linguistic diversity in their daily work routines as well as the associated problems and (both institutional and individual) solution strategies they describe.…”
Section: Methodsmentioning
confidence: 99%
“…A further differentiation in how foreign languages were used at the AMS arose between officials who drew on languages they learned after childhood, mainly standard school languages, and native speakers of common migrant languages (such as Turkish or Bosnian-Croatian-Serbian). Implicitly, a special and simultaneously ambiguous status was afforded to the latter (in detail see Holzinger, 2020): Although non-German counselling is not legally prohibited by the AMS, it was presented as undesirable. Interviewees described how this viewpoint was transmitted verbally by department managers and colleagues as well as through daily institutional routines.…”
Section: Using Languages Other Than German: An 'Emergency Solution' Only?mentioning
confidence: 99%
See 2 more Smart Citations
“…We did not have data on the nature and scope of their English language training either. A longitudinal study would be better in capturing the nuance of language use and challenges reflecting linguistic diversity and reality (Holzinger 2019). Our study was also conducted with immigrants only, without knowing how similar or different native English speakers use English in the workplace.…”
Section: Discussionmentioning
confidence: 99%